2017
DOI: 10.1590/s0102-8529.2017390100001
|View full text |Cite
|
Sign up to set email alerts
|

Neo-Agro-Colonialism, Control over Life, and Imposed Spatio-Temporalities

Abstract: Abstract:The control over what Dillon and Lobo-Guerrero (2008) conceptualise as 'pluripotent' life has become an essential factor of capitalist agriculture; this occurs through the regulation of strategic genetic resources. We recognise this course as part of a larger project of neo-agro-colonialism, which takes place by controlling both biotechnology and territories as an expression of a fungible power, turning geopolitics into biopolitics and vice-versa. While assessing the power relations and manipulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Prior studies in LMICs showed that the policy legacy of colonialism continues to constrain countries' ability to shift towards more sustainable food system policies (Chilowa, 1998; Labonté & Schrecker, 2007; McMichael, 2014; Pfrimer & Barbosa Junior, 2017; Raschke & Cheema, 2008; Thow et al, 2021). Our findings reflect on this path dependency and the challenges of shifting away from historical policy legacies resonate with this scholarship and highlight the importance of PICs' efforts of decolonising and regaining food sovereignty.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in LMICs showed that the policy legacy of colonialism continues to constrain countries' ability to shift towards more sustainable food system policies (Chilowa, 1998; Labonté & Schrecker, 2007; McMichael, 2014; Pfrimer & Barbosa Junior, 2017; Raschke & Cheema, 2008; Thow et al, 2021). Our findings reflect on this path dependency and the challenges of shifting away from historical policy legacies resonate with this scholarship and highlight the importance of PICs' efforts of decolonising and regaining food sovereignty.…”
Section: Discussionmentioning
confidence: 99%
“…Until the late 1990s, land occupations sought to denounce the impact of the latifundio (large land holdings) on social inequality in Brazil (Moreira 2012). Over the last two decades, however, the latifundio has been reconceptualised as a modern and entrepreneurial agribusiness that is mechanised and often uses technology, such as genetic sequencing technologies (Pfrimer and Barbosa Jr 2017), to increase efficiency and market competitiveness. As a result, land occupations no longer have the sole purpose of denouncing and combating unproductivity but also denouncing exclusion due to high productivity (Fernandes, Welch and Gonçalves 2014;Barbosa Jr and Coca 2015).…”
Section: The Struggle For Land As Exemplifying Disputes Over Agricult...mentioning
confidence: 99%
“…For further discussion on territory, see the work of Delaney (2005). 2 For more on the fungible nature of power see Pfrimer, Coca, and Barbosa Jr (2016) and Pfrimer and Barbosa Jr (2017). from a Platonian standpoint and, secondarily, as a space of circulation and integration following an Aristotelian perspective.…”
Section: Capitalist Agriculture and Its Strategic Assets: Land Agrobi...mentioning
confidence: 99%
“…As a result, this implies in an instrumentalisation of biotechnology that is turned into a tool for exerting power by controlling the various process of manipulating life for capital gain. The production of a bioeconomy relies on the manipulation of life to distort time in posit of temporalities more appropriate for global trade (PFRIMER; BARBOSA JR, 2017). This course engenders the construction of multiple spatialities of power, which will be analysed in the following section.…”
Section: Turning Life Into An Asset: Bioeconomics Biotechnology and T...mentioning
confidence: 99%